Effect of Audit Committee Tenure on Financial Reporting Quality of Listed Deposit Money Banks in Nigeria - Onyabe, Joseph Majiyebo; Okpanachi, Joshua; Nyor, Terzungwe; Yahaya, Onipe Adabenege; Ahmed, Mohammed (European Scientific Journal, ESJ, 2018)
This study examines the effect of audit committee tenure on financial reporting quality of listed deposit money banks in Nigeria. The study uses panel data obtained from the Nigerian Stock Exchange factbooks and the financial statements of 14 listed deposit money banks over a period of 10 years (2007-2016). The study uses cross sectional and time series research design. Financial reporting quality was measured using the modified Jones (1991) model and changes in working capital model, while audit committee tenure was measured as the mean tenure of audit committee members. The data was analyzed using descriptive (mean, standard deviation, minimum and maximum) and inferential statistics (correlation and regression analysis). The study reveals that audit committee tenure has a negative and insignificant effect on financial reporting quality under the two models. The implication of these results is that the tenure of audit committee members is not important when considering the financial reporting quality of deposit money banks in Nigeria. The study therefore concludes that the effect of audit committee tenure on financial reporting quality of deposit money banks in Nigeria is negative and insignificant. Based on this conclusion, the study recommends that further research should be conducted on other audit committee attributes in order to see which of the attributes may have significant effect on financial reporting quality.